Age-Dependence of Flow Homeostasis in the Left Ventricle - Benito, Yolanda; Martinez-Legazpi, Pablo; Rossini, Lorenzo; Pérez del Villar, Candelas; Yotti, Raquel; Martín Peinador, Yolanda; Rodríguez-Pérez, Daniel; Desco, M. Mar; Medrano, Constancio; Antoranz, Jose Carlos; Fernández-Avilés, Francisco; del Álamo, Juan C.; et al. (Frontiers in Physiology, 2019)
Background. Intracardiac flow homeostasis requires avoiding blood stasis and platelet activation during its transit through the cardiac chambers. However, the foundations of intraventricular blood washout and its exposure to shear stresses have been poorly addressed. We aimed to characterize and quantify these features in a wide population of healthy subjects and assess the relationships of these indices with age. Methods. We used color-Doppler echocardiography and custom post-processing methods to study 149 healthy volunteers from 26 days to 80 years old. From the intraventricular flow velocity fields we obtained personalized maps of 1) the residence time of blood in the LV, and 2) the shear index, a metric accounting for the strongest occurrence of shear stresses inside the chamber. From these maps we derived quantitative indices of the overall intraventricular blood washout and shear exposure. We addressed the age-dependence of these indices and analyzed their relationship with age-related changes in filling-flow. Results. The entire intraventricular blood pool was replaced before 8 cycles. Average residence time of blood inside the LV was less than 3 cycles in all subjects and followed an inverse U-shape relationship with age, increasing from median (IQR) of 1.0 (0.7 to 1.2) cycles in the 1st year of life to 1.8 (1.4 - 2.2) cycles in young adults (17-30 years old), becoming shorter again thereafter. Shear index showed no relation with age and was bounded around 20 dyn·s/cm2. Regions with the longest residence time and highest shear index were identified near the apex. Differences in the degree of apical penetration of the filling waves and the duration of the late-filling phase explained the age-dependence of residence time (R2adj = 0.48, p< 0.001). Conclusions. In average, blood spends 1 to 3 beats inside the LV with very low shear stress rates. The apical region is the most prone to blood stasis, particularly in mid-aged adults. The washout of blood in the normal LV is age-dependent due to physiological changes in the degree of apical penetration of the filling waves.